Study of the skills of balanced fund managers in Poland - Dorota Żebrowska-Suchodolska; Andrzej Karpio (Contemporary Economics, 2022)
The market timing is one of the active methods used by portfolio managers to do their investments more effective. It allows to separate management skills on a micro and macro scale. The market timing applies to the appropriate selection of assets for the portfolio and the right moment to change its structure. The aim of the presented research was to check whether the managers of balanced open-end mutual funds operating on the Polish market apply market timing skills. Nine balanced funds have been accepted for the research, which have existed since at least 2003 year. The research period covered the years 2003-2019. WIBOR 1M was used as the risk-free rate, and the market factors were the main WSE indexes. The research was first conducted based on basic market timing research models, i.e. the Henriksson-Merton and Treynor-Mazuy. Then, these models were expanded to include factors related to the bond market. The Henriksson-Merton and Treynor-Mazuy models and their extensions with additional factors were compared among themselves. Studies show that models with additional factors have proven to be more appropriate for balanced open-end mutual funds. It has occurred that regardless of the model used, market timing skills were similar. In most cases the fund managers did not achieve higher results than the results of the relevant benchmark. Managers tried to follow the trend rather than anticipate it. In most cases, there was also no ability to select assets or market-timing. Most of the parameters standing by these variables were not statistically significant.
Keywords: C01; C22; G14; 330; balanced mutual funds; management skills; market timing; selectivity